PERSEPSI MASYARAKAT TERHADAP KEHADIRAN PERGURUAN TINGGI DAN TINGKAT KESADARAN MASYARAKAT MELANJUTKAN PENDIDIKAN TINGGI (STUDI KASUS MASYARAKAT KEC. LANGSA LAMA, KOTA LANGSA) - Saragih, Deby Chintia; Jannah, Alfa Ichatul; Prasetyo, Okhaifi (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2023)
The purpose of conducting this study is none other than to find out the perceptions (views) of the community towards the presence of tertiary institutions (universities) and the level of public awareness of continuing higher education (a case study of the people of Langsa Lama District, Langsa City). In this study using descriptive qualitative research methods with a case study approach and the method of collecting sources used, namely secondary sources and primary sources, primary sources obtained directly from the object, namely the people of Langsa sub-district, long by way of direct interviews, observation and also documentation. Secondary sources can be through books, journal articles, theses, blogs and so on. Then the data analysis technique applied is divided into three stages, namely Data Reduction, Data Presentation and Drawing Conclusions. The results of this study show that (1). The public's perception (view) of the presence of tertiary institutions in the Langsa Lama District is very good for increasing the quality of human resources (HR). (2) The presence of tertiary institutions has had a very positive impact, including the impact of increasing the community's economy in Langsa Lama District, Langsa City. (2) The level of awareness of the people of Langsa Lama District, Langsa City about the importance of continuing their education to the tertiary level is quite good because the community already understands the importance of continuing their education to the tertiary level. The people in the Langsa Lama sub-district are aware that by continuing their education to tertiary institutions, their first goal is not just to find a job, but to study, add insight, increase intelligence, skills and knowledge obtained in college and then apply it in life to get a job at field.